The Risks of Prescription Drugs edited by Donald W. Light - Bauer, Henry H. (Journal of Scientific Exploration, 2013)
The traditional concern of anomalistics has been to demonstrate that its interests are substantive and worth attending to, within a wider social context that has treated mainstream science as a touchstone of an authenticity that anomalistics still has to earn. Increasingly over the last few decades, however, mainstream science has become less and less trustworthy as a result of excessive competition and concomitant dogmatism (Bauer 2012a). This has happened quite markedly in medical science and practice, and The Risks of Prescription Drugs describes this retreat from reliability. Complementary and alternative medicine have traditionally been decried by mainstreamers and their groupies on two related grounds: that any claimed successes of alternative treatments can be ascribed to the placebo effect rather than to the treatment, and that eschewing mainstream treatment robs patients of health-safeguarding, possibly life-saving benefits. The Risks of Prescription Drugs takes the wind out of both sails. Eschewing rather than accepting drug-based mainstream treatment can safeguard health and save lives. Moreover, the ability to summon the placebo effect is no mean feat and brings tangible benefits (Brody & Brody 2000).